Pengembangan media pembelajaran berbasis website materi trigonometri siswa SMA kelas XI - Ilham Fajar Anggoro; Tri Nova Hasti Yunianta (STKIP PGRI Banjarmasin, 2018)
This research purpose is develop a learning media website-based for trigonometry material. The subjects of this research were high school students of class XI. This type of research is Research and Development. The research and development model that used is ADDIE model with analyze, design, development, implementation, and evaluation stages. Website learning media has done for test validation process from material and display experts. This material aspects have average scores 4,0 with valid categories and for display aspects have average score 4,1 with valid categories. The media has also gone through practicality assessment tests achieve an average score 4.2 with practical categories. The media is tested on a small scale and get a positive responsse. After testing, the subject experienced an increase in cognitive value from the average value 37,4 to 76,8 the average value. The conclusion is website learning media that has been developed valid, practical, and effective for use in learning.